this can also be explained as b on edg
B. . . 72.8%. . . . . . . . .
C. . . 75%. . . . . . . . .
D. . . 81.7%. .
B. 2/5
C. 42/48
D. 245/1152
Answer:
Option C is correct.
Solution to the given system of equation is (6 , -8)
Step-by-step explanation:
Given the system of equation:
......[1]
.....[2]
Substitute the equation [1] in [2] we get;
Combine like terms;
Add 10 to both side of an equation:
Simplify:
Divide both sides by we get;
Simplify:
x = 6
Substitute the value of x =6 in equation [1] we get;
or
Simplify:
y = - 8
therefore, the solution to the given system of equation is; (6 , -8)
You can also see in the graph as shown below:
Answer:
18
Step-by-step explanation:
1/3 n = n - 12 Cross multiply
n = 3(n - 12)
n = 3n -36
2n = 36
n = 36/2
n = 18